Contemporary camareros: Santos sponsorship in the Philippines today - Tamayo, Jose Antonio Lorenzo L. (Animo Repository, 2020)
Filipino culture before the arrival of the Spaniards. With the coming of Christianity and the establishment of the Philippines as a Spanish colony, indigenous statues were replaced with Catholic images and icons, the santo. Records from the 17th to the 19th century show that missionaries relied on secular help in establishing a system of sponsorship for religious images. Those who sponsored santos were called camareros. This study aims to expand the work of Venida [1996, pp.500-513] and Galang [2012, pp.45-60], which focused on rural aristocracy and the traditional system of sponsorship for religious images established during the Spanish colonial period. Using anecdotes, personal interviews and a survey of camareros, the present study explores new systems of sponsorship for religious images in the twenty-first century, and describes the demographics, motivations, interactions, finances and santo collections of contemporary camareros. Keywords santo, camarero, religious images, anitos or likha, santo or poon, system of sponsorship, colonisation, ecclesiastical arts, Christianity, the Philippines, Spanish colonialism, social practices, rituals and festive events [ICH domain), traditional craftsmanship [ICH domain), social media, Facebook.